4-Day evaluation of the irritation potential of topical desoximetasone 0.25% and 0.05% spray on light-exposed skin. (19th May 2018) - Patel, Nupur U.; Grammenos, Alexandra; Gowda, Asha; Onikoyi, Omobola; Feldman, Steven R.
Abstract: Purpose: The safety and potential side effects of desoximetasone 0.25% and 0.05% sprays have not previously been studied. The primary objective of this study was to determine the irritation potential of desoximetasone 0.25%, 0.05% and vehicle sprays in response to irradiation. Materials and methods: Thirty-four subjects were enrolled in the study, each with three study treatments (desoximetasone 0.25%, 0.05% topical sprays and vehicle) were applied to two sites each on the back of every subject, with half of the sites irradiated with filtered UV light. Dermal reactions at the test sites were evaluated using a visual scale with corresponding numerical scores that rated the degree of erythema and oedema. Results: Desoximetasone 0.25%, 0.05%, and vehicle caused no detectable signs of phototoxicity when examined on days 3 and 4. Mean scores of desoximetasone 0.25%, 0.05% and vehicle to non-irradiated treatment areas showed no signs of irritation. Conclusions: Our results suggest that regular application of desoximetasone 0.25% and 0.05% topical sprays do not induce photosensitization or photoirritation. The safety of this topical spray may help with clinical management of patients using topical corticosteroids while also receiving therapeutic UV light exposure. Thus, patients can use desoximetasone sprays without concerns of side effects due to therapeutic light or sun exposure.